An analysis of atomic manipulation, intermolecular resolution and the artefacts of dynamic force microscopy - Lekkas, I. (2017)
In this thesis we go through a journey of atomic manipulation of Pb dimers on Si(100), then we examine the limitations of AFM in inter- molecular resolution and we take a closer look at a very promising technique named simultaneous STM/AFM which opens new horizons in the field but is part of an ongoing debate as it is still under development. NC-AFM imaging of adsorbed Pb dimers on Si(100) provided detailed information of the Pb configuration, which agrees with previous STM studies. The lateral force required to move a Pb dimer is related to the adsorption of the dimer on the surface, the associated potential energy land scape and in some cases the interaction of the Pb dimer with its neighbouring dimers. In the next part of this thesis, we examine the adsorption of a small organic molecule (NTCDI) on Si(111)-(7×7) and we report two energetically preferable geometries among others. In the last part of this thesis, we present an analysis of the crosstalk effect using an Omicron commercial qPlus sensor and a home built sensor with two system configurations and we compare them with a Createc commercial system. The results show that in order to avoid crosstalk the range of the STM operational pre-amplifier and the optimal elec- tronics wiring play a major role.